Determinant factors for malaria transmission on the coast of Oaxaca State, the main residual transmission focus in Mexico Factores determinantes de la transmisión de paludismo en la costa del estado de Oaxaca, el principal foco residual de transmisión en México - Juan E Hernández-Avila; Mario H Rodríguez; Angel F Betanzos-Reyes; Rogelio Danis-Lozano; Jorge F Méndez-Galván; Oscar J Velázquez-Monroy; Roberto Tapia-Conyer (Instituto Nacional de Salud Pública, 2006)
OBJECTIVE: The purpose of this study was to investigate the influence of demographic, socioeconomic and ecological factors in malaria transmission in the most important residual transmission focus in Mexico, located in the state of Oaxaca. MATERIAL AND METHODS: The extension of the focus was determined by a spatial and time analysis of the distribution of malaria cases in the state between 1998 and 1999 using a Geographical Information System. A malaria transmission intensity index (MTII) was constructed based on the total number of cases during the study period and the duration and frequency of transmission outbreaks within the villages. The relationship between local determinants and malaria transmission intensity was investigated using multinomial and ordered logistic models. RESULTS: The distribution of villages according to their MTII was: 325 high, 341 medium, 142 low and 717 with no transmission. Localities of high MTII were associated with areas having a tropical climate with summer rains and low water evaporation. Most high MTII villages were located in elevations between 200 and 500 m above sea level, in the area around Pochutla City. The amount of temporary streams in the neighborhood of localities had a highly significant positive association with the MTII. Distance to roads was only significant in the high malaria MTII stratum. CONCLUSIONS: The main factors determining malaria transmission in the focus are related to good conditions for the breeding of mosquito vectors. The existence of short-range population movements around Pochutla, the main economically active city in the area, indicates the necessity to implement a system of epidemiological surveillance to halt the dispersion of new outbreaks. OBJETIVO: Investigar la participación de factores demográficos, socio-económicos y ecológicos en la transmisión de la malaria en el foco de transmisión residual más importante en México, localizado en el estado de Oaxaca. MATERIAL Y MÉTODOS: La extensión del foco se determinó por medio de un análisis espacio-temporal de la distribución de casos de malaria en el estado entre 1998 y 1999, usando un Sistema de Información Geográfico. Un índice de intensidad de transmisión de malaria (MTII, por sus siglas en inglés) se construyó basado en el número total de casos durante el periodo del estudio y la duración y frecuencia de brotes de transmisión dentro de las localidades. La relación de determinantes locales con el MTII se investigó por medio de modelos multinomiales logísticos. RESULTADOS: La distribución de localidades según su MTII fue de 325 alto, 341 medio, 142 bajo y 717 sin transmisión. Localidades con MTII alto estuvieron asociadas a las áreas de clima tropical con lluvias en verano y evaporación baja. La mayoría de las localidades con MTII alto se localizaron a elevaciones entre 200 y 500 msnm, en el área alrededor de la ciudad de Pochutla. La cantidad de arroyos temporales en la vecindad de localidades tuvo una asociación positiva significativa con el MTII. La cercanía a carreteras de localidades con MTII alto fue significativa. CONCLUSIONES: Los factores principales que determinan la transmisión de la malaria en el foco están relacionados con las condiciones favorables para la cría de mosquitos vectores. La participación de movimientos de población de rango cortos alrededor de Pochutla, la principal ciudad económicamente activa en el área, indica la necesidad de implementar un sistema de vigilancia epidemiológica para detener la dispersión de nuevos brotes.